Bringing realism: Enhancing high-dimensional data for active behavior analysis in older adults - Guo, Cong; Jiang, Yaoqin; Yang, Yitong; Yuan, Zhilu; Guo, Renzhong (Journal of transport geography, 2025)
Understanding active travel behavior among older adults in suburban communities is often hindered by restricted data access and imbalanced sample distributions at the community level. These challenges limit the ability to train robust nonlinear models that capture the complex relationships between travel behavior and built environment characteristics. To address these issues, a data generation algorithm is proposed based on 7631 data points from a case study of the household travel survey in Xiamen, China, comparing the Variational Autoencoder (VAE) and Generative Adversarial Networks (GANs) to overcome data collection constraints and enhance predictive model performance and generalization accuracy. Applying a gradient boosting algorithm to the meticulously generated dataset improved data set accuracy by 20 % for the VAE model and 13 % for the GAN model, indicating that VAE surpasses other data augmentation methods and demonstrates superior performance. This effective synthetic framework helps researchers and practitioners in the field of active travel by enabling the creation and use of synthetic mobility data, which can be leveraged to address real-world challenges associated with decision-making in active travel behaviors.